Unilateral Brachial Plexus Lesion Impairs Bilateral Touch Threshold - Ramalho, Bia Lima; Rangel, Maria Luíza; Schmaedeke, Ana Carolina; Erthal, Fátima Smith; Vargas, Claudia D. (Frontiers in Neurology, 2019)
Unilateral brachial plexus injury (BPI) impairs sensory and motor functions of the upper limb. This study aimed to map in detail brachial plexus sensory impairment both in the injured and the uninjured upper limb. Touch sensation was measured through Semmes-Weinstein monofilaments at the autonomous regions of the brachial plexus nerves, hereafter called points of exclusive innervation (PEIs). Seventeen BPI patients (31.35 years±6.9 SD) and 14 age-matched healthy controls (27.57 years±5.8 SD) were tested bilaterally at six selected PEIs (axillary, musculocutaneous, median, radial, ulnar, and medial antebrachial cutaneous [MABC]). As expected, the comparison between the control group and the brachial plexus patients' injured limb showed a robust difference for all PEIs (p ≤ 0.001). Moreover, the comparison between the control group and the brachial plexus uninjured limb revealed a difference for the median (p = 0.0074), radial (p = 0.0185), ulnar (p = 0.0404), and MABC (p = 0.0328) PEIs. After splitting the sample into two groups with respect to the dominance of the injured limb, higher threshold values were found for the uninjured side when it occurred in the right dominant limb compared to the control group at the median (p = 0.0456), radial (p = 0.0096), and MABC (p = 0.0078) PEIs. This effect was absent for the left, non-dominant arm. To assess the effect of the severity of sensory deficits observed in the injured limb upon the alterations of the uninjured limb, a K-means clustering algorithm (k = 2) was applied resulting in two groups with less or more severe sensory impairment. The less severely affected patients presented higher thresholds at the median (p = 0.0189), radial (p = 0.0081), ulnar (p = 0.0253), and MABC (p = 0.0187) PEIs in the uninjured limb in comparison with the control group, whereas higher thresholds at the uninjured limb were found only for the median PEI (p = 0.0457) in the more severely affected group. In conclusion, an expressive reduction in touch threshold was found for the injured limb allowing a precise mapping of the impairment caused by the BPI. Crucially, BPI also led to reduced tactile threshold in specific PEIs in the uninjured upper limb. These new findings suggest a superordinate model of representational plasticity occurring bilaterally in the brain after a unilateral peripheral injury.